2021
DOI: 10.1371/journal.pone.0251709
|View full text |Cite
|
Sign up to set email alerts
|

Impact of medication therapy management service on selected clinical and humanistic outcomes in the ambulatory diabetes patients of Tikur Anbessa Specialist Hospital, Addis Ababa, Ethiopia

Abstract: Background Diabetes mellitus (DM) patients are at increased risk of developing drug therapy problems (DTPs). The patients had a variety of comorbidities and complications, and they were given multiple medications. Medication therapy management (MTM) is a distinct service or group of services that optimize therapeutic outcomes for individual patients. The study assessed the impact of provision of MTM service on selected clinical and humanistic outcomes of diabetes patients at the diabetes mellitus clinic of Tik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
(57 reference statements)
2
6
0
Order By: Relevance
“…The current study showed that 70.3% of hospitalized T2DM patients had at least one inappropriate anti-diabetic medication therapy with an average of 1.7 ± 0.46 IADTs. This is consistent with the prevalence’s of DRPs in patients with T2DM of 70% in the US [ 21 ], 71.9% in Ethiopia [ 44 ], 71.1% in India [ 45 ], and 73.7% in Pakistan [ 34 ]. On the other hand, the prevalence of DRPs in this study is lower than in the DRP studies in Malaysia (91.8% and 90.5%) [ 20 , 46 ], Nigeria (94%), Australia (96%), and Switzerland (100%) [ 25 , 47 , 48 ].…”
Section: Discussionsupporting
confidence: 85%
“…The current study showed that 70.3% of hospitalized T2DM patients had at least one inappropriate anti-diabetic medication therapy with an average of 1.7 ± 0.46 IADTs. This is consistent with the prevalence’s of DRPs in patients with T2DM of 70% in the US [ 21 ], 71.9% in Ethiopia [ 44 ], 71.1% in India [ 45 ], and 73.7% in Pakistan [ 34 ]. On the other hand, the prevalence of DRPs in this study is lower than in the DRP studies in Malaysia (91.8% and 90.5%) [ 20 , 46 ], Nigeria (94%), Australia (96%), and Switzerland (100%) [ 25 , 47 , 48 ].…”
Section: Discussionsupporting
confidence: 85%
“…The current study showed that 70.3% of hospitalized T2DM patients had at least one inappropriate anti-diabetic medication therapy with an average of 1.7 ± 0.46 IADTs. This is consistent with the prevalence's of DRPs in patients with T2DM of 70% in the US [21], 71.9% in Ethiopia [44], 71.1% in India [45], and 73.7% in Pakistan [34]. On the other hand, the prevalence of DRPs in this study is lower than in the DRP studies in Malaysia (91.8% and 90.5%) [20,46], Nigeria (94%), Australia (96%), and Switzerland (100%) [25,47,48].…”
Section: Discussionsupporting
confidence: 89%
“…4 Systematic reviews and meta-analysis of randomised controlled trials have demonstrated the effects of pharmacist-led care in patients with T2DM, but majority of these studies were conducted in high income countries (HICs) and only complimented by few from LMICs. [4][5][6][7][8][9][10][11][12] Literature search identified four published randomised-controlled trials among patients with DM in Nigeria within the last decade. [13][14][15][16][17] None of the study was done in the northern part of the country.…”
Section: Introductionmentioning
confidence: 99%